Study of the magnetic response to the AGW propagation based on measurements at the Akademik Vernadsky station - Alla Fedorenko; Evgen Kryuchkov; Anna Voitsekhovska; Ihor Zhuk (Ukrainian Antarctic Journal, 2024)
To find the electromagnetic response to the propagation of atmospheric gravity waves (AGWs), wave fluctuations of the magnetic field were studied according to measurement data at the Ukrainian Antarctic Akademik Vernadsky station. We analysed continuous data for three components of the geomagnetic field of January–March 2024. We considered wave fluctuations of the magnetic field in the period range of 5–60 min, which correspond to medium-scale AGW in the atmosphere. From January–March, a total of 500 wave events were analysed. The amplitudes ranged from ~one nT to several tens of nT. Two dominant period groups were observed: ~5–12 minutes (including the Brunt–Väisälä period) and 25–30 minutes. We suppose that this pattern indicates a different origin of the AGW. This new result indicates the experimental possibility of separating the effects of AGW influences “from below” and “from above”. Time intervals during the day when magnetic field fluctuations are observed most often were determined. In all three magnetic field components, fluctuations are observed simultaneously in the evening. In geomagnetically quiet conditions, there is a daily asymmetry in the frequency of occurrence of meridional and zonal disturbances. Wave activity in the meridional Bx and vertical Bz components is registered mainly in the morning and evening. In the component By, wave disturbances prevail in the daytime from 10 to 14 hours (UT) and are also observed in the evening. In March 2024, there were two geomagnetic storms during which the amplitudes of magnetic field fluctuations increased simultaneously in different period ranges. The fluctuations may be caused by modulation of polar current systems and/or dynamo-current generation during the propagation of AGW at heights in the E-region of the ionosphere. Further studies are needed to establish which mechanism contributes more to the phenomenon.